Needs-based food and nutrient security indices to monitor and modify the food supply and intakes: Taiwan, 1991–2010. (November 2015) - Peng, Cheau-Jane; Lee, Meei-Shyuan; Wahlqvist, Mark L.; Pan, Wen-Harn; Lee, Wen-Chung; Lin, Chin; Guo, How-Ran
Highlights: Supply-to-needs ( S-Nr ) and intake-to-needs ( I-Nr ) ratios were developed. S-Nr and I-Nr allow recognition of excess/inadequate supply/intakes or combination. Food security indices (FSI) can be expressed as geometric means (GMs) of the S-Nr . Nutrient security indices (NSI) can be expressed as geometric means (GMs) of the I-Nr . FSI or NSI indicates how well the food or nutrient supply meets population needs. Abstract: Background: To track Taiwanese food and nutrient supplies and population intake of them against the nutrition recommendations by food security indices that warn about food insecurity. Methods: We used food balance sheets from 1991 to 2010 to estimate food and nutrient supplies and data from 1993–1996 ( n = 3915) to 2005–2008 ( n = 2908) Taiwanese Nutrition and Health Surveys to assess intake of Taiwanese population. Age-and-gender specific Food Guides and Dietary Reference Intakes were multiplied by the population size and then summed to determine food and nutrient needs. Food Security Indices (FSIs) and Nutrient Security Indices (NSIs) were defined as the geometric means of supply-to-needs ratio ( S-Nr ) and intake-to-needs ratio ( I-Nr ) with reference to an ideal of 1.0. Higher values indicate potential food insecurity. Results: From 1997 to 2010, the S-Nr for most food categories and nutrients decreased; dairy products and vegetables fell below recommendations in 2010. For food intake, all except cereals/roots increased between the two surveys, but only vegetables and soy/fish/meat/egg met the needs in 2005–2008. For both surveys, high FSIs for dairy (2.16, 2.26) were due to low supply and low intake, and those for soy/fish/meat/egg (1.78, 1.91) to oversupply and overconsumption. The FSIs for fruit improved from 1.50 to 1.17, with a smaller supply but more consumption. NSIs explained the FSIs. Conclusion: FSIs and NSIs capture composite information about the food supply, intake, and recommendations, which allows food security to be monitored with action-points of 1.0 for food and nutrition policy.